2006
DOI: 10.1111/j.1472-765x.2006.01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus strains on cancer cell proliferation and oxidative stress in vitro

Abstract: Aims:  The objective of this study was to assess in vitro, whether heat‐killed (HK) lactic acid bacteria cells and fractionations of HK cells could suppress the viability of human cancer cells and inhibit the cytotoxicity associated with oxidative stress. Methods and Results:  Among the strains, the HK cells of Lactobacillus acidophilus 606 and Lactobacillus casei ATCC 393 exhibited the most profound inhibitory activity in all of the tested cell lines. HK cells of L. acidophilus 606 were determined to be less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
149
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(154 citation statements)
references
References 20 publications
2
149
0
3
Order By: Relevance
“…Smears of DNA fragments were detected, which were indicative of necrotic cells in the cell population, whereas the PI staining and fluorescence microscopy examination indicated that the soluble polysaccharide fraction induced apoptosis, rather than necrosis, in the cancer cells (33).…”
Section: Discussionmentioning
confidence: 97%
“…Smears of DNA fragments were detected, which were indicative of necrotic cells in the cell population, whereas the PI staining and fluorescence microscopy examination indicated that the soluble polysaccharide fraction induced apoptosis, rather than necrosis, in the cancer cells (33).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, there are several references in the literature telling us that probiotic bacteria, especially Lactobacillus and Bifidobacterium, elicit a strain-specific cytokine pattern through their ability to interact with the IEC (Morita et al, 2002;Bahrami et al, 2010;Boesten et al, 2011). The inhibitory effects of probiotics upon the proliferation of several colon cancer cell lines have been previously demonstrated (Choi et al, 2006). Ewaschuk et al (2006) reported that Lactobacillus acidophilus, L. (Ewaschuk et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Lactic acid bacteria (LAB) such as Lactobacillus acidophilus are important microorganisms in the intestines of healthy humans (10). LAB are considered to be beneficial microorganisms and have been associated with multiple potential health effects in both humans and animals (11)(12)(13)(14).…”
Section: Ardiovascular Disease (Cvd) Is the Leading Cause Of Death Inmentioning
confidence: 99%